Multi-Symplectic Method for the Zakharov-Kuznetsov Equation (Advances in Applied Mathematics and Mechanics, 2018)
A new scheme for the Zakharov-Kuznetsov (ZK) equation with the accuracyorder of $\mathcal{O}(∆t^2+∆x+∆y^2)$ is proposed. The multi-symplectic conservation propertyof the new scheme is proved. The backward error analysis of the new multi-symplecticscheme is also implemented. The solitary wave evolution behaviors of the Zakharov-Kunetsovequation are investigated by the new multi-symplectic scheme. The accuracyof the scheme is analyzed.